Use of the grey relational analysis to determine optimum laser cutting parameters with multi-performance characteristics - Caydas, Ulas; Hascalik, Ahmet (Elsevier Sci Ltd, 2008)
This paper presents an effective approach for the optimization of laser cutting process of St-37 steel with multiple performance characteristics based on the grey relational analysis. Sixteen experimental runs based on the Taguchi method of orthogonal arrays were performed to determine the best factor level condition. The response table and response graph for each level of the machining parameters were obtained from the grey relational grade. In this study, the laser cutting parameters such as laser power and cutting speed are optimized with consideration of multiple-performance characteristics, such as workpiece surface roughness, top kerf width and width of heat affected zone (HAZ). By analyzing the grey relational grade, it is observed that the laser power has more effect on responses rather than cutting speed. It is clearly shown that the above performance characteristics in laser cutting process can be improved effectively through this approach. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: laser cutting; grey relational analysis; characteristics; multi-performance characteristics